Potential Role of Macrophage Phenotypes and CCL2 in the Pathogenesis of Takayasu Arteritis - Kong, Xiufang; Xu, Ming; Cui, Xiaomeng; Ma, Lingying; Cheng, Huiyong; Hou, Jun; Sun, Xiaoning; Ma, Lili; Jiang, Lindi (Frontiers in Immunology, 2021)
Objectives: To investigate vascular macrophage phenotype as well as vascular and peripheral chemokine (C-C motif) ligand 2 (CCL2) expression during different stages of disease progression in patients with Takayasu Arteritis (TA). Methods: In this study, 74 patients with TA and 50 controls were recruited. TA disease activity was evaluated with Kerr scores. Macrophage phenotype and CCL2 expression were examined by immunohistochemistry in vascular specimens from 8 untreated and 7 treated TA patients, along with 4 healthy controls. Serum CCL2 were quantified by enzyme-linked immune-absorbent assay from TA patients at baseline (n=59), at 6-months (n=38), and from 46 healthy volunteers. Vascular macrophage phenotype, vascular CCL2 expression and serum CCL2 levels during different stages, as well as the relationship between serum CCL2 and disease activity or other inflammatory parameters (erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and interleukin 6 (IL-6)) were investigated. Results: In untreated patients, vascular M1 macrophages and CCL2 showed increased expression, mainly in the adventitia. In contrast, in treated patients, vascular adventitial M1 and CCL2 expression were decreased, while vascular medial M2 macrophages and CCL2 levels were increased. Distribution of macrophages and CCL2 was consistent within the TA vascular lesions regardless of the disease stage. Furthermore, peripheral CCL2 was elevated in patients with TA (TA: 160.30 ± 120.05 vs. Control: 65.58 ± 54.56 pg/ml, P < 0.001). CCL2 levels were found to correlate with ESR, CRP, and IL-6 (all R values between 0.55 and 0.6, all P < 0.001). Receiver operating curve analysis demonstrated that CCL2 (at the cut-off value of 100.36 pg/ml) was able to predict disease activity (area under the curve = 0.74, P = 0.03). Decrease in CCL2 level was observed in patients with clinical remission (CR), but not in patients without CR, after 6 months of treatment (CR patients: baseline 220.18 ± 222.69 vs. post-treatment 88.71 ± 55.89 pg/ml, P = 0.04; non-CR patients: baseline 142.45 ± 104.76 vs. post-treatment 279.49 ± 229.46 pg/ml, P = 0.02). Conclusions: Macrophages contribute to vascular pathological changes in TA by undergoing phenotype transformation. CCL2 is an important factor for recruiting macrophages and a potential biomarker for disease activity.